Full-scale application and performance of a low-consuming system for decentralized village domestic wastewater treatment. (April 2022) - Cheng, Fangkui; Wang, Chenchen; Wen, Cangxiang; Wang, Siyu; Cheng, Helai; Shen, Shuting; Lu, Xiwu
Abstract: Rural domestic wastewater (RDW) management has always been challenging due to the vast range and decentralized household distribution. This study constructed a full-scale system combined with source-separated pretreatment and terminal bio-eco treatment for a village RDW treating. The process of the application was designed from the perspective of low consumption in energy and device. The performance of the biological units consisted of an anoxic filter (ANF) and multi-stage waterwheel driving rotating biological contactors (ms-wdRBCs) was investigated. ANF/ms-wdRBCs with HRTANF 12 h and HRTms-wdRBCs 1.5 h performed best in pollutants' removal at 200% reflux ratio (RR). The maximum flow rate (FR) that the system could burden is 0.6 m 3 /h with a 42% increase from the designed FR 0.42 m 3 /h, which shows the potential in coping with the future increase of individual RDW generation. Meanwhile, the source separation and primary treatment could effectively reduce the pollutant load entering the biologic units. In the four consecutive seasons' operating, 84.9 ± 3.1% COD, 87.6 ± 3.5% NH4 + -N, 44.2 ± 3.1% TN, and 28.2 ± 2.0% TP are removed, respectively. Seasonal water temperature (WT) variation is found to have a remarkable effect on biological treatment. NH4 + -N removal is found the most sensitive index of pollutant removal to RR, FR, and WT variating. The system has shown the reliability of the year-round running. The full-scale application could serve as a sustainable prototype for the village RDW treatment. Graphical abstract: Unlabelled Image Highlights: Full-scale anoxic filter/multi-stage waterwheel driving RBCs were evaluated. Seasonal water temperature variation had obvious effects on pollutant removal. Bio-eco treatment with source-separated pretreatment constantly worked well.